GROWTH PERFORMANCE OF INTENSIVELY RAISED INDIGENOUS CHICKENS FED DIETS WITH DIFFERENT PROTEIN LEVELS - Akhmat Rizkuna; Roosena Yusuf; Amani Aldiyanti; Novemia Fatmarischa (Faculty of Animal Science, University of Tulang Bawang, 2025)
This study aimed to evaluate the effect of dietary protein levels on the growth performance of intensively raised indigenous chickens. A total of 168 day-old chicks (DOC) with an initial body weight of 28.68 ± 1.13 g were used in the experiment. The study was arranged in a completely randomized design (CRD) consisting of four treatments with six replications. The treatments were based on different protein levels during the starter and finisher phases: T0 (22%–15%), T1 (18%–16%), T2 (18%–16%–14%), and T3 (18%–16%–14%). The parameters measured included feed intake, body weight gain (BWG), final body weight, and average daily gain (ADG). Data were analyzed using analysis of variance (ANOVA) to determine the effect of treatments on the observed parameters. The results showed that dietary protein levels had no significant effect (P>0.05) on total feed intake. However, they significantly affected (P<0.05) body weight gain. The T0 treatment with higher protein in the starter phase yielded the best performance, with BWG of 819.53 g/bird, final body weight of 848.21 g/bird, and ADG of 11.71 g/bird/day. These values were higher than those of T1, T2, and T3. It can be concluded that providing a high-protein diet during the starter phase improves the growth performance of indigenous chickens, particularly final body weight and ADG, without increasing feed intake. This finding highlights the importance of formulating diets based on nutrient requirements during the early growth phase to support optimal performance of intensively reared indigenous chickens. Keywords: Indigenous chicken, Feed intake, Body weight gain, Dietary protein level.